People’s Multiparty Democracy and Democratization of the Left Movement - Oli, KP Sharma (State, Society and Development: PMPD Perspectives, 2025)
People’s Multiparty Democracy (PMPD), propounded by People’s Leader Madan Bhandari, has had a profound influence on Nepal’s political trajectory since its conceptual articulation in the late 1980s and its formal adoption by the Communist Party of Nepal (Unified Marxist-Leninist) at its Fifth General Convention in 1993. As a distinct ideological innovation, this doctrine has revitalized the communist movement in Nepal providing a democratic framework capable of accommodating democratic aspirations. This study critically examines PMPD as a unique, Nepali version of Marxism. Employing a mixed methodology that combines qualitative analysis, historical inquiry, and autobiographical reflection, the research draws on both primary and secondary sources, as well as the author’s lived experience as a participant-ideologue in the development of PMPD under Bhandari’s leadership. The findings underscore PMPD not merely as a Nepali version of Marxism but as a democratically grounded and ideologically inclusive framework. Moreover, PMPD is presented as an outmatched alternative to both one-party communist authoritarianism and neoliberal capitalist imperialism— offering a model in which state power remains subject to periodic democratic validation, protection of human rights, and the pursuit of socio-economic justice. As PMPD continues to evolve as a progressive ideological paradigm, it holds significant potential to reinvigorate the global communist movement through its synthesis of Marxist-Leninist principles, democratic pluralism, and key elements of New Democracy.